(untitled) (Baghdad Science Journal, 2017)
This study aimed to identify the histological changes of mosquito fish (Gambusia affinis) exposed to vydate pesticide. (48) female fishes were collected from local markets and also from the stream that surround Baghdad university campus at Al-jadyria, fishes divided into (4) groups and each group consist of 12 fish: T1(exposed to 0.0000001 mg/L),T2 (exposed to 0.0000002 mg/L ) and T3 (exposed to 0.000001 mg /L) of vydate pesticide for (8) weeks. As well as a control group. Fishes were dissected for histological preparations after each (2,4,6,8) weeks of exposure time. Gills were fixed by Bouin’s fluid and stained with Hematoxylin and eosin. Histological study showed that the structure of gill in a control group consists of primary and secondary gill lamellae appeared parallel and oblique. The secondary gill lamellae lined with squamous epithelial and pillar cells, and each secondary lamellae have capillary derived from blood vessel in primary lamellae, chlorid cells and few mucous cells found between secondary lamellae. The histological alterations in gills included hyperplasia of chloride cells, congestion of blood vessels, lamellar disarray, lifting of epithelial cells, Oedema, fusion of adjacent secondary lamella and Aneurysm. Results concluded that vydate had a vicious effect on gills and caused severe histological alterations such as hyperplasia of chloride cells and simple alterations such as lamellar disarray, and also these histological changes commensurate direct proportion with concentrations were used in this study.